The Promoting Role of HK II in Tumor Development and the Research Progress of Its Inhibitors - Bingru Liu; Yu Lu; Ayijiang Taledaohan; Shi Qiao; Qingyan Li; Yuji Wang (Molecules, 2023)
Increased glycolysis is a key characteristic of malignant cells that contributes to their high proliferation rates and ability to develop drug resistance. The glycolysis rate-limiting enzyme hexokinase II (HK II) is overexpressed in most tumor cells and significantly affects tumor development. This paper examines the structure of HK II and the specific biological factors that influence its role in tumor development, as well as the potential of HK II inhibitors in antitumor therapy. Furthermore, we identify and discuss the inhibitors of HK II that have been reported in the literature.